SCCmec typing of clinical isolates Staphylococcus haemolyticus / Farhan Haziq Azharollah and Aziyah Abdul-Aziz - Azharollah, Farhan Haziq; Abdul-Aziz, Aziyah (Faculty of Applied Sciences, 2019)
A total number of 38 clinical strains of Staphylococcus haemolyticus originally obtained from Hospital Tuanku Ampuan Rahimah, Klang Selangor, were used in this study. The antimicrobial susceptibility of these nosocomial pathogens was tested against penicillin and cefoxitin. Except for one strain (B200) which was sensitive, the rest of the isolates were resistant to penicillin. Similarly, only one strain (F4) was sensitive against oxacillin while the rest were resistant. For cefoxitin, 34 or 89.5% of the isolates were resistant to this antibiotic and classified as Methicillin resistance Staphylococcus haemolyticus (MRSH). Amplification of the mecA gene showed among the MRSH strains 19 or 55.9% harbour the mecA gene but 15 or 44.1% were found negative for this gene. This could be due to the mec gene complex which does not only consist of the mecA gene but could also harbour other classes of mec genes such as mecB, mecC, mecD or mecE. However, one of the Methicillin-sensitive Staphylococcus haemolyticus (MSSH) strains susceptible against cefoxitin was also found to harbour the mecA gene. All the 20 isolates positive for mecA gene were further subjected to Staphylococcal Cassette Chromosome mec (SCCmec) type I, II, III, IV and V. The results showed that two or 10.0% of the strains (B14 and R27) expressed SCCmec type II while only one isolate (P29) expressed SCCmec type III. For the remaining 17 isolates, SCCmec typing was not detected suggesting that these isolates do not harbour SCCmec I, IV or V. Hence, there is a possibility that these isolates carry other types of SCCmec.